Ceramic interconnect technology handbook (CRC Press/Taylor & Francis, 2007)
Ceramics were among the first materials used as substrates for mass-produced electronics, and they remain an important class of packaging and interconnect material today. Most available information about ceramic electronics is either outdated or focused on their materials science characteristics. The Ceramic Interconnect Technology Handbook goes beyond the traditional approach by first surveying the unique properties of ceramics and then discussing design, processing, fabrication, and integration, as well as packaging and interconnect technologies